Improving Science Learning Outcomes with Hands-On-Minds-On Learning Model on The Third Graders Of Elementary School - Rohaenah, Ike Nilawati; Ngadiyem, Ngadiyem; Hasbudin, Dinan; Fauzi, Fauzi; Dewie, Prahasinta (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
Hands-On-Minds-On as a learning approach involves activities and direct experiences with natural environment or educational experiences that actively involve students in manipulating objects to gain knowledge or understanding to reform and improve science learning outcomes by using Hands-On-Minds-On learning model for third grade students at SDN Tengah 07 Pagi. The total number is 42 students, 20 students were taken as sample population. Based on the result of the first pre-cycle research, it was found that 13 students did not reach the Minimum Completeness Criteria (KKM), and students who obtained above the Minimum Completeness Criteria (KKM) were 7 students. From the result of the pre-cycle research, it was found that the value of Class III A is still relatively low with an average score of 60.75. Whereas, the Minimum Completeness Criteria (KKM) for science subject is 65. In the second cycle, teacher includes more learning media, makes classroom situation more enjoyable and provides many opportunities for students to be active in learning process. Finally, the learning outcomes also increase from the average students’ learning outcomes of 78.50 to 85.25. Therefore, it can be concluded that the research cycle I and cycle II can improve the students’ learning outcome on science learning in class III A by using the Hands-On-Minds-On learning model. Thus, the research ends in the second cycleHands-on Minds On sebagai pendekatan pembelajaran yang melibatkan aktivitas dan pengalaman langsung dengan lingkungan alam atau pengalaman pendidikan yang secara aktif melibatkan siswa dalam memanipulasi objek untuk mendapatkan pengetahuan atau pemahaman. Untuk memperbaiki dan meningkatkan hasil belajar IPA dengan menggunakan model Hands On Minds On pada siswa kelas III di SDN Tengah 07 Pagi. Jumlah seluruh 42 siswa ,diambil sebagai populasi sampel 20 Siswa Berdasarkan hasil penelitian prasiklus pertama diperoleh hasil 13 siswa tidak mencapai KKM, dan siswa yang memperoleh nilai di atas KKM berjumlah 7 siswa. Dari hasil penelitian prasiklus tersebut diperoleh hasil bahwa nilai IPA Kelas III A masih tergolong rendah dengan rata-rata nilai yang diperoleh 60,75. Sedangkan KKM untuk mata pelajaran IPA adalah 65. siklus ke dua guru menambahkan media pembelajaran menjadi lebih banyak, membuat situasi ruang kelas lebih menyenangkan dan memberikan banyak kesempatan siswa untuk aktif dalam pembelajaran. Akhirnya hasil pembelajaran pun meningkat dari rata-rata hasil belajar siswa 78,50 menjadi 85,25.  Berarti dapat disimpulkan bahwa penelitian siklus I dan siklus II dapat meningkatkan hasil belajar IPA siswa kelas III A dengan menggunakan model pembelajaran Hands On Minds On sehingga penelitian berakhir pada siklus II.